Problem-Solving Ability of Female Students with Moderate Cognitive Level in Function Relation - Nugroho, Muhamad; Setyawati, Rina Dwi; Sutrisno, Sutrisno (Journal of Mathematical Pedagogy (JoMP), 2021)
This study aims to determine the problem-solving abilities of female students with moderate cognitive levels in function relations. The subjects of this study were students in grade 8 of junior high school who were taken purposively. Two female students with moderate cognitive levels were obtained. Data collection techniques using written methods and interviews. The data analysis technique uses three stages: data reduction, data presentation, and conclusions drawing. Checking the validity of the data using the triangulation method by comparing the written test data and interviews. In this study, management and data analysis used the NVivo software. This study shows that female students with a moderate cognitive level can carry out systematic problem-solving procedures, including understanding problems, planning, implementing plans, and checking back properly. However, these students have not been able to solve the problem correctly.